Поняття та види принципів-заборон у системі основоположних засад трудового права України - Старчук, О.; Starchuk, О. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті визначено систему засадничих ідей трудового права України та проаналізовано її складові. Встановлено, що у системі принципів однойменної галузі права важливе місце займають принципи, які спрямовані на дотримання трудових прав громадян (принципи-заборони), до яких належать: заборона дискримінації у сфері праці, заборона примусової праці, заборона дитячої праці. Охарактеризувано трудове законодавства та міжнародні стандарти, у нормах яких відображено принципи-заборони у сфері регулювання трудових відносин. The article deals with the basic ideas of labor law system of Ukraine and its components are analyzed. In the market the basis classification of labor law principles should be based on the main categories of natural law: equality and freedom, on the one hand, and on the other, labor law and its actual state implementation have been grounded. The system of this branch of law principles are important and direct to maintain citizen labor rights (prohibition principles), which include: discrimination prohibition in the sphere of employment, forced labor prohibition, child labor abolition have been highlighted. The prohibition principles in the sphere of employment is determinant, because it is provided free labor and legal equality of the labor relationship participants have determined.
Concept and Types of Prohibition Principles in the System of Labor Law Fundamental Basis of Ukraine
Keywords: принципи права; засадничі ідеї трудового права; заборона дискримінації; дитяча праця; дитяча праця; principles of law; the basic idea of labor law; discrimination prohibition; child labor; forced labor